Enhancing the role of occupational health services in the battle against Corona Virus disease 2019 - Chirico, F.; Sacco, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Occupational risk assessment is the core of any practice in occupational health and safety at the workplace. In Italy, the implementation of the preventive measures required by law (DPCM of April 26, 2020 and subsequent modifications and integrations) can exempt the employers from legal disputes in case of COVID-19 infection among employees. However, these laws have made meaningless the risk assessment process, which is the ideal setting where the preventive and protective measures must be identified and enhanced by individual employers, in collaboration with health and safety managers and occupational physicians, in the true exposure conditions. In this commentary, the authors stressed the role of workplace risk assessment and occupational health services for the valuable contribution that they may give to the battle against COVID-19, in terms of prevention, contact-tracing activity and COVID-19 rates of vaccinal coverage.